Analysis of the factors determining the distribution of heritage sites in Portugal - Mourao, Paulo (Bulletin of Geography. Socio-economic Series, 2025)
While all places have their own historical and cultural wealth, not all areas have the same number of points of tourist interest. Classified objects of heritage are a case in point: some places have a high concentration of classified heritage objects, while others do not. This article discusses the heterogeneity of objects classified as heritage of public interest in Portugal. In addition to a descriptive analysis, we estimated models for explaining this heterogeneity. The dimensions most responsible for such a phenomenon are those related to the centrality of places, their economic dynamism, and their touristic vocation. We found that variables like the centrality of a place, being close to the Spanish border, or having decentralised delegations of certain ministries impact the number of tangible and intangible cultural heritage objects. We further explore these outcomes by considering their serious challenges for less dense areas.